Differential neuropilin isoform expressions highlight plasticity in macrophages in the heterogenous TME through in-silico profiling - Han, Hyun-Jee; Rubio-Alarcon, Marcos; Allen, Thomas; Lee, Sunwoo; Rahman, Taufiq (Frontiers in Immunology, 2025)
IntroductionThe nuanced roles of neuropilin (NRP) isoforms, NRP1 and NRP2, have attracted considerable scientific interest regarding cancer progression. Their differential expressions across various cancer types are specific to NRP isoforms which are shown in a cancer type-dependent manner. It accounts for the different mechanisms involved, driven by a co-expression of gene-sets associated with overexpressed NRP1 or NRP2. Their different expressions on tumour-associated macrophages (TAMs) with disparate markers are associated with the heterogenous tumour microenvironment (TME) through their plasticity and pro-tumorigenic activities.MethodsSingle-cell RNA sequencing (scRNA-seq) analyses were performed on tumours from clear cell Renal Cell Carcinoma (ccRCC) and skin cutaneous melanoma (SKCM) which exhibit the highest expressions of NRP1 and NRP2, respectively. Datasets were processed using established bioinformatics pipelines, including clustering algorithms, to determine cellular heterogeneity and quantify NRP isoform expression within distinct macrophage populations. Using differential gene expression analysis (DEGA) alongside co-enrichment studies, we explored gene-sets associated with NRP1 or NRP2 overexpression in TAMs.ResultsOur analysis revealed a marked upregulation of NRP1 in TAMs isolated from ccRCC and elevated NRP2 expression in SKCM-derived TAMs. Both NRP1+ and NRP2+ macrophages showed an M2-like polarisation characterised by immune suppression and extracellular matrix degradation. Coupled with the previously uncharacterised NRP isoform specific- subpopulations within these cancers identified by DEGA, co-enrichment analyses demonstrated that the upregulation of gene-sets associated with NRP1 is associated with angiogenesis and tumour progression through VEGF signalling, while gene-sets with NRP2 showed dual functionality in the TME-dependent manner. Their distinct roles in regulating macrophage plasticity, tumour invasion, and metastasis were highlighted.DiscussionThese findings underscore distinct isoform-specific mechanisms by which NRP1 and NRP2 contribute to TAM-mediated cancer progression. This study aims to establish a foundation for future research, leading to biological experiments with focused gene-sets derived from our findings. This approach can contribute to the development of immunomodulatory strategies targeting specific NRP isoforms in macrophages, tailored to individual cancer types and abnormal expressions of those gene markers, potentially offering a more effective therapeutic approach compared to broad-spectrum NRP inhibition strategies.